The Role of Planning Standards in Sustaining Residential Community Analytical Study of The Growing Standard - Sana Sati Abbas; Ghooson Najem Abdulzahra (Iraqi Journal of Architecture and Planning, 2018)
Planning standards are considered as one of important concepts. The role of such standards appear in guiding the sustainable development plans , and the transformation to sustainable residential communities .So, the research problem which arised is that there is a knowledge gab about the role of the growing standard in achieving sustainability in residential community.The research studies the sustainable residential community, in order to deduce the main indicators related to it , which include (social , economic , environment and physical standards). The paper focused on the physical standards only,so research hypothesis is represented by : "the growing standard is a standard, which can achieve sustainability in residential communities through the flexibility in area standards for housing plots and the variation in housing options according to the changing in the family need".So the paper depends on the flexibility of the standard as a main concept for the research to achieve the variety in the housing options as a main indicator for measuring flexibility in the planning standard which can sustain residential community. This variable had been used in case study in (Al- Qahira Quarter) in Baghdad City .The paper prepared questionair for data collection , and test hypothesis to reach the findings, conclusions and recommendations .Keywords :Planning Standards , Housing Policy , The Growing Standard , The Residential Community , Flexibility and Diversity